2021
DOI: 10.1161/circresaha.121.318982
|View full text |Cite
|
Sign up to set email alerts
|

Laminar Flow on Endothelial Cells Suppresses eNOS O-GlcNAcylation to Promote eNOS Activity

Abstract: Rationale: In diabetic animals as well as high glucose cell culture conditions, endothelial nitric oxide synthase (eNOS) is heavily O-GlcNAcylated, which inhibits its phosphorylation and nitric oxide (NO) production. It is unknown, however, whether varied blood flow conditions, which affect eNOS phosphorylation, modulate eNOS activity via O-GlcNAcylation-dependent mechanisms. Objective: The goal of this study was to test if steady laminar flow, but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 68 publications
2
16
2
Order By: Relevance
“…In AML12 cells, azaserine decreased UDP-GlcNAc by 50% ( Figure 3 C), which is similar to that observed in three endothelial cell lines. 33 , 34 , 35 …”
Section: Resultsmentioning
confidence: 99%
“…In AML12 cells, azaserine decreased UDP-GlcNAc by 50% ( Figure 3 C), which is similar to that observed in three endothelial cell lines. 33 , 34 , 35 …”
Section: Resultsmentioning
confidence: 99%
“…SGLT2i effects on eNOS activity are also not always observed, which also could be related to differences in mechanical and metabolic conditions applied to the ECs in the separate studies. For example, hyperglycaemic or oscillating flow conditions induce O-GlcNAcylation of the eNOS enzyme, thereby preventing that increases in enzyme activity can occur [ 84 ]. Finally, differences in measurement sensitivity between research laboratories may also have its impact.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, overall glycolytic flux could be altered by changes in flux down glycolysis side branch pathways, including glycogen synthesis and the PPP. We previously showed that flow decreases endothelial glucose flux down the hexosamine biosynthetic pathway, which impacts nitric oxide production [ 38 ]. In this study, we observed increased glucose flux down the uronic acid pathway, which could be used to create more proteoglycans and glycosaminoglycans.…”
Section: Discussionmentioning
confidence: 99%
“…A custom-built cone-and-plate device was used to apply shear stress to HUVECs [ 38 ]. The device generates flow by rotating the cone around an axis perpendicular to the plate [ 47 ].…”
Section: Methodsmentioning
confidence: 99%